PENGARUH BENDING DAN ANECHOIC CHAMBER PADA ANTENA MIKROSTRIP BINTANG 21 TERHADAP RETURN LOSS,VSWR DAN BANDWIDTH DENGAN ORIENTASI BENDING ARAH SUMBU Y - Muhammad Fathan Romadhon; Muhammad Fauzan Edy Purnomo; Ali Mustofa (Jurnal Mahasiswa TEUB, 2023)
Mikrostip antennas have various dimensions and placements that depend on needs. In some antennas, especially antennas placed on uneven surfaces, it can allow bending of the microstrip antenna which can affect the characteristics or parameters of the antenna. In this study, a microstrip antenna with a 21-star patch with a staircase shape on a groundpalne that worked at a frequency of 2.4 GHz. Design and simulation were carried out using CST studio suite 2021 software and measurement were carried out with nanoVNA SAA2. The simulation results show that bending causes degradation in the microstrip antenna parameters which include return loss and vswr. On the contrary, the measurement results show that there is an increase in performance on the return loss and vswr parameters. The results of the antenna measurements carried out in the anechoic chamber did not have a significant effect on the vswr parameters, return loss, bandwidth and impedance. Radiation pattern, polarization, gain, and other antenna parameters related to radiation in free space are the right parameters to be measured in the anechoic chamber. Keywords :Microstrip, Bending, Return Loss, VSWR, Bandwidth, Impedance, Anechoic Chamber